2014
DOI: 10.1177/0013164414539163
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Classroom Observation Scores

Abstract: Observations and ratings of classroom teaching and interactions collected over time are susceptible to trends in both the quality of instruction and rater behavior. These trends have potential implications for inferences about teaching and for study design. We use scores on the Classroom Assessment Scoring System-Secondary (CLASS-S) protocol from 458 middle school teachers over a 2-year period to study changes over time in (a) the average quality of teaching for the population of teachers, (b) the average seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 25 publications
10
100
1
5
Order By: Relevance
“…On average, raters assessed the overall quality of classrooms slightly above the midpoint on the 7-point scale. This is consistent with prior research that has tracked overall classroom quality scores using the CLASS over a two-year period (Casabianca et al, 2015). Intraclass correlation coefficients (ICCs) showed that the majority (89%) of variability in classroom quality was at Level 1.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…On average, raters assessed the overall quality of classrooms slightly above the midpoint on the 7-point scale. This is consistent with prior research that has tracked overall classroom quality scores using the CLASS over a two-year period (Casabianca et al, 2015). Intraclass correlation coefficients (ICCs) showed that the majority (89%) of variability in classroom quality was at Level 1.…”
Section: Resultssupporting
confidence: 88%
“…The unconditional intercept model estimated an overall mean in classroom quality assessments of 4.22 (SE = .04). This is just above the midpoint on the 7-point rating scale, as was found in Study 1 and in recent longitudinal data on the CLASS (Casabianca et al, 2015). ICCs showed that the majority (93%) of variability in classroom quality was at Level 1.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…It is equally vital to develop systems for periodic calibration to ensure that raters' scores continue to be consistent with expert scores Park et al, 2014). Park and colleagues (2014) found that systems developed to minimize rater bias based on the characteristics of the rater, teacher, and classroom were effective-but in the context of video observations when raters were not personally connected to the teachers.Even rigorous training and calibration systems may not be sufficient in reducing variability in scores, especially when stakes are attached (Casabianca et al, 2013(Casabianca et al, , 2015. In consequential evaluations of teachers, North Carolina observers tended to rate a disproportionate numbers of teachers just above proficiency thresholds (Barrett Crittenden-Fuller & Guthrie, 2015).…”
mentioning
confidence: 99%
“…In addition, although some studies have found that structured observation protocols can be applied with adequate reliability, others have raised questions about the consistency of ratings and the validity of scores obtained from these tools for different purposes (Harris and Sass, 2007;Henry, Murray, and Phillips, 2007;HRI, 2000;Jacob and Lefgren, 2008;Kane, Kerr, and Pianta, 2014;Learning Mathematics for Teaching Project, 2011;Medley and Coker, 1987;Piburn and Sawada, 2000;Schultz and Pecheone, 2014;Walkington and Marder, 2014). Rater error is a major threat to the reliability and validity of classroom observation scores and principal ratings, despite great effort to train raters and calibrate their scoring (Casabianca, Lockwood, and McCaffrey, 2015;Myford, 2012;Whitehurst, Chingos, and Lindquist, 2014). Using Classroom Assessment Scoring System data from the recent Measures of Effective Teaching project, Drew Gitomer and his colleagues found that observers had difficulty agreeing on ratings of certain dimensions of teaching, particularly those for which teacher performance was generally relatively weak (Gitomer et al, 2014).…”
Section: Limitations Of Direct Classroom Observationmentioning
confidence: 99%